2013
DOI: 10.1371/journal.pone.0070251
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Responses by Swine Primary Bronchoepithelial Cells Are Limited Compared to Human Bronchoepithelial Cells Following Influenza Virus Infection

Abstract: Swine generate reassortant influenza viruses because they can be simultaneously infected with avian and human influenza; however, the features that restrict influenza reassortment in swine and human hosts are not fully understood. Type I and III interferons (IFNs) act as the first line of defense against influenza virus infection of respiratory epithelium. To determine if human and swine have different capacities to mount an antiviral response the expression of IFN and IFN-stimulated genes (ISG) in normal huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 57 publications
(62 reference statements)
3
22
0
Order By: Relevance
“…Tracheal tissue was obtained from a fetal Holstein cow of the age of 4 months gestation under aseptic conditions (Wang et al, 2012). Th e bovine fetal primary tracheal epithelial cells were separated, cultured, and cryopreserved according to the methods described by Hauser et al (2013). 293T cells and BHK-21 cells were obtained from the American Type Culture Collection and grown in Dulbecco's modifi ed Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…Tracheal tissue was obtained from a fetal Holstein cow of the age of 4 months gestation under aseptic conditions (Wang et al, 2012). Th e bovine fetal primary tracheal epithelial cells were separated, cultured, and cryopreserved according to the methods described by Hauser et al (2013). 293T cells and BHK-21 cells were obtained from the American Type Culture Collection and grown in Dulbecco's modifi ed Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…The PK-1 cell line was acquired from ATCC (#CL-101). The isolation, culturing and differentiation of primary NSBE has been described previously [30] . NSBE cells were verified by University of Georgia Veterinary Medical Diagnostic Laboratory (VMDL) as PCR-negative for influenza, circovirus and porcine reproductive respiratory syndrome virus before use.…”
Section: Methodsmentioning
confidence: 99%
“…Virus stocks of selected reassortants were analyzed in PK-1 cells, MDCK cells, undifferentiated normal swine bronchoepithelial cells, fully differentiated normal swine bronchoepithelial (dNSBE) cells, and fully-differentiated normal human bronchoepithelial (dNHBE) as described [30] , [39] at an MOI = 0.01 for 24, 48, 56 and 72 hpi. All viral titers were determined by the 50% tissue culture infectious dose (TCID 50 ) assay [40] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Swine primary lung epithelial cells have also been used to characterize innate immune responses to IAV infection [15] and the reassortment tendencies of IAV in co-infected cells [16]. Previous results have shown that primary swine lung epithelial cells compared to the immortalized porcine kidney epithelial cell line (PK-1) give rise to different reassortment outcomes after co-infection when introducing human pandemic H1N1 and swine H3N2 [16].…”
Section: Influenza a Virus (Iav)mentioning
confidence: 99%